Suggestions for the facilitation of olympic weightlifting teaching and coaching methods (part 1, The Power Clean). - van Herk, R. J. P.; de Vries, L.-E. (Journal of Australian Strength and Conditioning, 2020)
The power clean is a prominent exercise for the development of strength and power in athletes from a wide range of sporting disciplines and performance levels. For optimal performance enhancement and injury prevention, this complex compound exercise requires adequate coaching. Despite the popularity of this Olympic lift in strength and conditioning programs, the most effective teaching and coaching strategies are yet to be identified. The purpose of this study is to contribute to this process. The focus will be on methodical segmentation of the power clean, the identification of Olympic weightlifting principles and the practical applications for teaching and coaching. For didactical purposes, it is suggested to apply the concept of chaining to three intentional actions of the power clean, clear the knees, explode and catch, and to rely on the process of self-organisation, instead of deliberate practice, for the coordination of the involuntary transitional movements (e.g. the scoop). Furthermore, to efficiently teach and coach the technical execution of the power clean, it is suggested to focus on the following four Olympic weightlifting principles; creating the shortest upward barbell trajectory, maximising proximity of the barbell, maximising barbell speed and moving fluently. Subsequently, methodical progressions, efficient verbal cueing, categorical exercise differentiation, implicit coaching strategies, and conclusions and practical applications are discussed.